Sagot :
Answer:
2 + 9(3) = 29
Step-by-step explanation:
just substitute 9 for n then multiply by 3 then add 2
Answer:
Step-by-step explanation:
Simplifying
2n + 3 = 9
Reorder the terms:
3 + 2n = 9
Solving
3 + 2n = 9
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '-3' to each side of the equation.
3 + -3 + 2n = 9 + -3
Combine like terms: 3 + -3 = 0
0 + 2n = 9 + -3
2n = 9 + -3
Combine like terms: 9 + -3 = 6
2n = 6
Divide each side by '2'.
n = 3
Simplifying
n = 3